Content analysis of process based writing in web-supported environment at bits Pilani and its possible implications - Luhach, Suman (BELT - Brazilian English Language Teaching Journal, 2016)
A digital environment for instructional purposes has been adopted in the form of a Learning Management System (LMS) by educational institutions. The present study facilitates incorporation of online writing tutorials over LMS ‘Nalanda’ BITS Pilani with the objective of understanding the nature of the writing process while students accomplish their writing tasks on online forums. A paragogical framework has also been devised by keeping scaffolding as the theoretical basis of learning. The methodological strategy adopted to realize the objective and analyze the impact of the educational intervention was content analysis. Results of the content analysis, under the parameters corresponding to different stages of the writing process, suggest that students’ emphasis had been more on content development and critical thinking.